Response of a comprehensive cancer center to the COVID-19 pandemic: the experience of the Fondazione IRCCS–Istituto Nazionale dei Tumori di Milano. Issue 3 (June 2020) - Valenza, Franco; Papagni, Gabriele; Marchianò, Alfonso; Daidone, Maria Grazia; De'Braud, Filippo; Colombo, Mario Paolo; Frignani, Andrea; Galmozzi, Gustavo; Ladisa, Vito; Pruneri, Giancarlo; Salvioni, Roberto; Spada, Pierangelo; et al.
Background: The rapid spread of coronavirus disease (COVID-19) is affecting many countries. While healthcare systems need to cope with the need to treat a large number of people with different degrees of respiratory failure, actions to preserve aliquots of the healthcare system to guarantee treatment to patients are mandatory. Methods: In order to protect the Fondazione IRCCS–Istituto Nazionale dei Tumori di Milano from the spread of COVID-19, a number of to-hospital and within-hospital filters were applied. Among others, a triage process to detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) positivity in patients with cancer was developed consisting of high-resolution low-dose computed tomography (CT) scan followed by reverse transcription polymerase chain reaction (RT-PCR) detection of SARS-CoV-2 in nose–throat swabs whenever CT was suggestive of lung infection. To serve symptomatic patients who were already admitted to the hospital or in need of hospitalization while waiting for RT-PCR laboratory confirmation of infection, a COVID-19 surveillance zone was set up. Results: A total of 301 patients were screened between March 6 and April 3, 2020. Of these, 47 were hospitalized, 53 needed a differential diagnosis to continue with their cancer treatment, and 201 were about to undergo surgery. RT-PCR was positive in 13 of 40 hospitalized patients (32%), 14 of 52 day hospital patients (27%), and 6 of 201 surgical patients (3%). Conclusion: Applying filters to protect our comprehensive cancer center from COVID-19 spread contributed to guaranteeing cancer care during the COVID-19 crisis in Milan. A surveillance area and surgical triage allowed us to protect the hospital from as many as 33 patients infected with SARS-CoV-2.